Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Siswa pada Tema 1 Subtema 1 di Kelas III SD Negeri Percontohan 091317 Pematang Raya - Lasrida Lumban Batu; Lisbet N. Sihombing; Eva Pasaribu (Medan Resource Center, 2022)
The Effect of Problem Based Learning Learning Model on Student Learning Outcomes in Class III SD Negeri Pilot 091317 Pematang Raya. manuscript. UHKBPNP University Primary School Teacher Education and Education Studies Program. Advisor I Lisbet Novianti Sihombing, S.Pd., M.Pd and Advisor II Eva Pasaribu, S.Pd., M.Pd. This research will be conducted to find out whether the results of the Problem Based Learning Learning Model are consistent with student learning outcomes. This type of refining is a quasi-experimental which involves two lobes treated with pekkaduan berda. The population in this study were third grade students of SD Negeri Pilot 091317 Pematang Raya and two classes were selected by cluster random sampling as the research sample, namely classes IIIA and IIIB. Class IIIA is the experimental class that uses the Problem Based Learning Expenditure Model, while class IIIB is the control class that uses conventional belebajang. The research instrument used for learning ability. The data that has been built using the instrument was analyzed using technical descriptive statistics and inferential.